Migration distances in Russia: a demographic profile of migrants - Liliya B. Karachurina; Nikita V. Mkrtchyan (Baltic Region, 2023)
The distance of migration is closely linked to life course events, which are, in turn, marked by age. It serves as a criterion for distinguishing migration from other forms of spatial mobility. This paper aims to calculate the average distance of domestic migrations in Russia between 2011 and 2020, considering various migrant profiles such as sex, age, and type of residential registration. The Euclidean distance between 130,000 geocoded Russian settlements was computed to estimate migration distances. These geospatial data enabled us to obtain estimations of migration distances by weighting the total distance of all migrations based on their respective numbers. The distance of internal migration was similarly estimated, taking into account age, sex, and type of residential registration. The findings revealed that 31.3 % of domestic residential relocations occurred within very short distances not exceeding 50 km, while 43.5 % took place within 100 km of the previous place of residence. Calculating the average migration distance allowed us to identify two peaks: one at the ages of 22—23, present only for men, and another at the ages of 50—70. In all other cases, there were no sex-specific differences in migration distances. Migrants who obtained permanent registration at their new place of residence tended to cover greater distances compared to those registered only temporarily. The shortest relocation distances were associated with the age of 16, which could be attributed to prospective students moving to the nearest town where a vocational school is located.